The real Nemo movie: Description of embryonic development in Amphiprion ocellaris from first division to hatching. Issue 11 (7th May 2021) - Salis, Pauline; Lee, Shu‐hua; Roux, Natacha; Lecchini, David; Laudet, Vincent
Abstract: Background: Amphiprion ocellaris is one of the rare reef fish species that can be reared in aquaria. It is increasingly used as a model species for Eco‐Evo‐Devo. Therefore, it is important to have an embryonic development table based on high quality images that will allow for standardized sampling by the scientific community. Results: Here we provide high‐resolution time‐lapse videos to accompany a detailed description of embryonic development in A ocellaris . We describe a series of developmental stages and we define six broad periods of embryogenesis: zygote, cleavage, blastula, gastrula, segmentation, and organogenesis that we further subdivide into 32 stages. These periods highlight the changing spectrum of major developmental processes that occur during embryonic development. Conclusions: We provide an easy system for the determination of embryonic stages, enabling the development of A ocellaris as a coral reef fish model species. This work will facilitate evolutionary development studies, in particular studies of the relationship between climate change and developmental trajectories in the context of coral reefs. Thanks to its lifestyle, complex behavior, and ecology, A ocellaris will undoubtedly become a very attractive model in a wide range of biological fields. Key Findings: Six periods have been identified to describe the embryonic development of the false clown‐fish Amphiprion ocellaris. We provide a staging series organized similarly to other models allowing comparative stud‐ies of embryonic development. We provide high‐resolution time‐lapse videos to accompany a detailed description of embry‐onic development in Amphiprion ocellaris. These data provide a general framework that can be used as a tool to standardize studies and experimental procedures throughout false clownfish development.